CHARACTERIZATION OF METAL WORKING FLUIDS USING TRIBOLOGICAL TESTING METHODS - Ostrowicki, Nicolai; Markert, Johannes; Hanenkamp, Nico (MM Science Journal, 2021)
The objective of this paper is to determine whether it is possible to compare the lubricating properties of different Metal working fluids (MWF) for a defined cutting application using easily reproducible tribological tests. The idea is that this will eventually allow users of MWF to select the most suitable MWF for a specific application without the need to run expensive and time-consuming tests on a machine tool being unavailable for production during that time. The test method chosen is the Pin-on-Disc (PoD) test, as there has been extensive research and an easy setup can be acquired inexpensively, making it more available and attractive for potential users. The PoD-tests were done with two groups of MWF, those for wet machining and those for minimum quantity lubrication (MQL). Additionally, the viscosity of the MQL-MWF has been measured using a capillary viscometer. The evaluation of the wear on the pins and discs with different measuring devices shows consistent and promising results for the comparison of MQL-MWF, while the MWF for wet machining display only limited comparability with the PoD-setup used.
CRIS-Team WoS Importer:2021-11-26

Effect of various cooling lubricant strategies on turning Inconel 718 with different cutting materials - Ostrowicki, Nicolai; Kaim, Alexander; Gross, Daniel; Hanenkamp, Nico (Procedia CIRP, 2021)
Due to its resistance to high temperatures and corrosion, Inconel 718 has a wide range of applications, particularly in the chemical and aerospace industry. The aim of this study is to investigate the potential of turning Inconel 718 with regard to tool life, depending on various cooling lubricant strategies and cutting materials. The reference process is flood cooling with carbide tools. Based on this, the process with carbide and CBN tools under dry machining, cryogenic cooling and cryogenic minimum quantity lubrication will further be investigated. Cutting forces, tool wear, roughness and chips are analyzed. Cutting length, surface quality and sustainability can be improved by using CBN and cryogenic minimum quantity lubrication (CMQL).<br
Keywords: Inconel 718; CBN; turning; cryogenic; cryogenic minimum quantity lubrication

Investigation of the influence of lubricating oils on the turning of metallic materials with cryogenic minimum quantity lubrication - Gross, Daniel; Bigelmaier, Matthias; Meier, Trixi; Amon, Sven; Ostrowicki, Nicolai; Hanenkamp, Nico (Procedia CIRP, 2019)
Nowadays, cooling and lubrication for cutting processes in industry are mostly based on flood cooling. The enormous quantities of lubricants are not only harmful for the environment and employees, but also require additional infrastructure and pre-treatment, while processed parts require an additional cleaning step due to metallic swarf which leads to high manufacturing costs. The cryogenic minimum quantity lubrication could serve as an alternative cooling and lubrication concept, which might be suitable for high-alloyed steels and titanium alloys as well. Within this work the potential of this new concept of cooling and lubrication was investigated by the utilization of different lubricants for turning of Ti6Al4V, X5CrNi18-10 and 42CrMo4 workpieces with a main focus on cutting forces, tool wear and resulting surface roughness. Required data indicates that the cryogenic minimum quantity lubrication might indeed be suitable to replace the conventional wet processing routes. The proper lubricants are selected to match the material to be machined.<br
Keywords: Turning; Cryogenic Machining; Minimum Quantity Lubrication; Ti6Al4V; 42CrMo4; X5CrNi18-10